Access to information and use of it as a dimension of preparedness for hospital practice among Malaysian housemen - Abd. Manaf, Noor Hazilah; Omar, Azura; Mohd, Dinon; Ismail, Izhairi; Abdul Hamid, Zabeda; Adeyemi, Adewale Abideen (2013)
Much concern has been raised regarding the preparedness of newly graduated medical officers for hospital practice. The concern is granted given the fact that incompetency and medical error may, and can, lead to grave consequences. The housemanship period is a two-year training programme for newly graduated medical officers aimed at building competency and preparation for hospital practice. It is also a transition period between medical school and hospital practice. A national study was carried out with the objective to explore the level of preparedness for hospital practice among housemen in Malaysian hospitals. Data obtained (N=1213) were subjected to statistical analysis by using SPSS. Access to information and IT were among the six dimensions of preparedness for hospital practice; with the rest being interpersonal skills, basic skills and continuing professional development, holistic skills, coping skills, ethic and legal skills, patient management skills, scientific knowledge, and clinical skills.